Acaricidal Properties of Four Neem Seed Extracts (Azadirachta indica) on the Camel Tick Hyalomma dromedarii (Acari: Ixodidae) - Gareh, Ahmed; Hassan, Dalia; Essa, Asmaa; Kotb, Saber; Karmi, Mohammed; Mohamed, Abou El-Hamd H.; Alkhaibari, Abeer Mousa; Elbaz, Elzahara; Elhawary, Nagwa M.; Hassanen, Eman A. A.; Lokman, Maha S.; El-Gohary, Fatma A.; et al. (Frontiers in Veterinary Science, 2022)
Tick infestation remains one of the major health problems that affect the productivity and comfort of camels. The control of ticks mainly relies on using chemical acaracides. Limited information is available on the potential benefits and activity of various neem extracts on Hyalomma ticks. The present study investigated the acaricidal activity of neem seed extracts at different concentrations against developmental stages of the camel tick Hyalomma dromedarii in comparison to Butox and diazinon. The acaricidal activity of three extracts, namely, hexane extract (HE), methyl chloride extract (MCE), and methanol extract (ME), of neem seeds (Azadirachta indica) were tested at varying concentrations of 5, 10, 15, and 20% on engorged H. dromedarii female ticks at days 1, 3, 5, 7, 12, 16, 20, 28, 37, and 43 after treatment (DPT). Interestingly, results of applying different neem seed extracts to engorged H. dromedarii female ticks showed that the most effective extract was hexane at concentration 20%, causing 100% mortality at 1st day post-application, while methanol extract at 20% and dichloromethane extract at 20% caused the death of all ticks at 28th day posttreatment as compared to Butox® 5.0 and Diazinon-60, which resulted in mortality of all ticks at 3 and 5 DPT, respectively. In addition, no mortality was reported with the application of aqueous extract (AE), which served as the control group. Furthermore, the neem hexane extract exhibited high efficacy against reproductive performance of female ticks, whereas no fertility or oviposition was reported at all of their concentrations. Additionally, no hatchability occurred using all neem extracts, except the aqueous extract, which showing no effect. In the present study, larvae responded more rapidly to the plant extracts, whereas mortality of all larvae was recorded at 24 h after treatment with 5% hexane. Taken together, this study pointed out that the acaricidal effect of hexane extract of neem seeds was more effective and could be economically used for controlling H. dromedarii ticks.